MIRERC 062/2025: Assessment of Selected Laboratory Quality Management Essentials in the Haematology Department at Meru Teaching and Referral Hospital - Muthomi Rugendo, Ian; Dr. Zakayo Maingi; Dr. Titus Mutwiri, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Despite the critical role of accurate haematological testing in patient diagnosis and care, national audits reveal significant deficiencies in process control, facilities and safety, and equipment management, with Meru County scoring below national averages .This study aims to address these gaps by examining process control practices, assessing the adequacy of facilities and safety measures, and examining equipment management practices using the WHO’s Stepwise Laboratory Quality Improvement Process Towards Accreditation (SLIPTA) checklist. Employing a descriptive cross-sectional design, the study will involve laboratory technologists and technicians, utilizing census sampling, data collection through standard operating procedures, quality manuals, interviews, and observations, and analysis via SPSS with descriptive and inferential statistical tests. The findings will enhance diagnostic accuracy, inform hospital management and policy decisions, and contribute to academic research, ultimately improving patient outcomes at MeTRH.